Pertumbuhan Stek Mawar (Rosa damascena Mill.) Pada Waktu Perendaman Dalam Larutan Urine Sapi - Nur Hafizah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
Rose is known as an ornamental plant that can be used for various purposes such as ornamental plants in the garden , in pots , flowers used as blushes , perfume, cosmetics and medicine. Cuttings are often doomed to failure with no root growth. One attempt to overcome failure in root growth on cuttings is to provide an organizing grow. Cow urine is one that contains a growth hormone indole 3 - butyric acid belongs to the class of auxin . Cow urine is a synthetic growth hormone is commonly used to stimulate root growth in cutting. This study aims to (i) determine the growth of cuttings of roses against time of immersion in a solution of cow urine, (ii) get marinade’s best rose cuttings in a Solutions of cow urine. This research was conducted in the village of Banua Lawas District Tabalong South Kalimantan in April to July 2014, using a single factor RAK, with level 6 treatments with 4 replications in order to get 24 units of the experiment . Factors tested were cow urine soaking time ,ie p0 = without soaking , p1 = 15 minutes , p2 = 30 minutes , p3 = 4 minutes , p4 and p5 = 60 minutes = 75 minutes . The results showed that treatment of cow urine soaking time significantly affected the speed variables emerged shoots, shoot length 2 mst age, number of leaves mst age 2 and 4, as well as the very significant effect on long shoots 6 mst age and number of roots, the best treatment was achieved in p1 with 15 minutes soaking time .